Stratigraphy and Chronology of Sodicho Rockshelter – A New Sedimentological Record of Past Environmental Changes and Human Settlement Phases in Southwestern Ethiopia - Hensel, Elena A.; Vogelsang, Ralf; Noack, Tom; Bubenzer, Olaf (Frontiers in Earth Science, 2021)
The preservation of archaeological remains and environmental information in a sediment accumulation can vary in caves and rockshelters, depending on external climatic conditions, and the circumstances within the shelter. Several sediment stratigraphies in the Horn of Africa are characterized by erosion layers, discordances and chronological gaps, that create uncertainties about the impact of climatic and environmental shifts on human settlements. Archaeological sites in Ethiopia that preserve information about human occupation during the Upper Pleistocene and Holocene often deal with major gaps during a period corresponding to MIS 2. In this study we present the first results of sedimentological, geochemical analyses and radiocarbon dating at Sodicho Rockshelter (1930 m above sea level) that provide evidence on high altitude settlement during this mentioned chronostratigraphic gap and subsequent time slices. This new archaeological site in the southwestern Ethiopian Highlands hosts a two-meter-long sediment record. So far, a stratigraphy has been excavated that dates back to ~ 27 ka, including several settlement phases of Late Pleistocene and Holocene hunter-gatherers and providing information on environmental changes. A multiproxy approach was chosen to establish a first general stratigraphy of the site and to disentangle the sediment composition as well as site formation processes. The results suggest a variation of allochthonous and autochthonous geogenic deposits, and anthropogenic accumulation processes. With the help of radiocarbon dating, anthropogenic layers were dated covering the arid Last Glacial Maximum (LGM, ~ 21 ± 2 ka). The occupation phases were interrupted in cause of environmental changes. The most prominent is the accumulation of reddish, archaeological sterile deposits that can be chronologically associated with the African Humid Period (AHP, ~ 15–5 ka BP). Geochemical records point to dry spells within this humid phase, suggesting correlations with regional climate signals of lacustrine sediments. These sediment accumulations of past wet conditions are covered by alternating layers of Holocene volcanic fallout and sediments with preserved cultural material. Our study provides a preliminary impression of still poorly understood time periods of human occupation in the southwestern Ethiopian Highlands. The data obtained from Sodicho Rockshelter could validate the current state of knowledge and partially reduce the chronostratigraphic gap.